2010
DOI: 10.1111/j.1462-2920.2009.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Strict cospeciation of devescovinid flagellates and Bacteroidales ectosymbionts in the gut of dry‐wood termites (Kalotermitidae)

Abstract: SummaryThe surface of many termite gut flagellates is colonized with a dense layer of bacteria, yet little is known about the evolutionary relationships of such ectosymbionts and their hosts. Here we investigated the molecular phylogenies of devescovinid flagellates (Devescovina spp.) and their symbionts from a wide range of dry-wood termites (Kalotermitidae). From species-pure flagellate suspensions isolated with micropipettes, we obtained SSU rRNA gene sequences of symbionts and host. Phylogenetic analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 58 publications
1
71
0
Order By: Relevance
“…nifH homologs in capillary-picked flagellates Cloning and sequence analysis of the eukaryotic SSU rRNA genes in the capillary-picked suspensions of D. arta and S. tabogae confirmed the purity of the preparations. The sequence of D. arta was identical to that obtained in a previous study of the same termite (FN377761; Desai et al, 2010); the newly obtained SSU rRNA gene sequence of S. tabogae has been submitted to GenBank (FN649413).…”
Section: Nitrogen Fixation In Dry-wood Termites Ms Desai and A Brunementioning
confidence: 48%
See 3 more Smart Citations
“…nifH homologs in capillary-picked flagellates Cloning and sequence analysis of the eukaryotic SSU rRNA genes in the capillary-picked suspensions of D. arta and S. tabogae confirmed the purity of the preparations. The sequence of D. arta was identical to that obtained in a previous study of the same termite (FN377761; Desai et al, 2010); the newly obtained SSU rRNA gene sequence of S. tabogae has been submitted to GenBank (FN649413).…”
Section: Nitrogen Fixation In Dry-wood Termites Ms Desai and A Brunementioning
confidence: 48%
“…There is abundant evidence that the bacterial symbionts of most gut flagellates are specific for and even co-speciate with their respective hosts (for example, Stingl et al, 2005;Noda et al, 2006Noda et al, , 2007Noda et al, , 2009Ikeda-Ohtsubo et al, 2007;Ohkuma et al, 2007;Ikeda-Ohtsubo and Brune, 2009;Desai et al, 2010;Strassert et al, 2010). The nitrogenfixing nature of the bacterial symbionts has been documented for at least two of these symbiotic pairs (Hongoh et al, 2008b and this study) and may indeed be the evolutionary driver for many of these associations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Other members of the termite-specific cluster in Figure 2 included uncultured phylotypes recovered from the cells of the protist Oxymonas sp. in the gut of Cryptotermes secundus (Desai et al, 2010). In the present study, we identified members of this cluster as intranuclear symbionts of both oxymonad and parabasalid protists ( Figure 5).…”
Section: Discussionmentioning
confidence: 77%